Preparation of a New Heavy Metal Chelating Agent and Its Removal of Copper Ions in Wastewater - Zhang, Siyang; Zhang, Kaibin; Yang, Guo; Zhang, Fuping; Jiang, Liang; Gao, Chao; Yuan, Hui (International Journal of Materials Science and Technology Studies, 2024)
In this study, a new type of dithiocarbamate (DTCs) heavy metal chelating agent MF-DTC was prepared by carbon disulfide modified melamine formaldehyde resin prepolymer, and the structure of the chelating agent and chelating products was characterized by infrared, ultraviolet, elemental analysis, thermogravimetry, scanning electron microscopy and other means: the process of chelating agent Cu was studied, and the results showed that MF-DTC chelating agent had a higher adsorption capacity, and compared with the traditional chelating agent SDD and Na2S, it had higher chelating capacity under acidic conditions, it can be directly used to treat heavy metals in acidic wastewater. Moreover, the environmental stability of heavy metals after chelation is high. Heavy metals are not easy to be leached again after treatment.